System for Simultaneous Control of Multiple Unmanned Aerial Vehicles - Yehor Zheliazkov (Proceedings of the International Conference on Applied Innovations in IT)
Nowadays, airspace is a strategically important resource for both national security and economic development. The state is responsible for its efficient use and safety. One of the key challenges of today is countering unmanned aerial vehicles, which includes the use of electronic warfare, laser weapons and other technologies. The popularity of drones is growing rapidly not only in the consumer sector, but also in industry, agriculture, energy, geodesy, and military. Military conflicts demonstrate a significant increase in the use of unmanned aerial vehicles, in particular in the form of drone swarms, which creates new challenges for countermeasures. One of the most promising developments is the creation of a platform for managing heterogeneous swarms of drones, including those that were previously hostile but can be integrated into their own system. It provides new opportunities for warfare and an advantage in the management of military operations. This paper presents solutions that provide simultaneous control over heterogeneous unmanned aerial vehicles, which makes it difficult to use them effectively in modern warfare and defense strategies. An approach is realized as real prototype electronics circuit, which can create a flexible platform capable of intercepting, analyzing and integrating enemy unmanned aerial vehicles into its own network through electronic interference, hacking communication protocols and reprogramming. The results of proposed approach case study showed the possibility to take under the control “enemie’s” unmanned aerial vehicles to the control of main operator.